Biochemical and HDX Mass Spectral Characterization of the SARS-CoV-2 Nsp1 Protein - Mishra, Nawneet; Kant, Ravi; Leung, Daisy W; Gross, Michael L; Amarasinghe, Gaya K (Biochemistry (Easton), 2023)
A major challenge in defining the pathophysiology of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is to better understand virally encoded multifunctional proteins and their interactions with host factors. Among the many proteins encoded by the positive-sense, single-stranded RNA genome, nonstructural protein 1 (Nsp1) stands out due to its impact on several stages of the viral replication cycle. Nsp1 is the major virulence factor that inhibits mRNA translation. Nsp1 also promotes host mRNA cleavage to modulate host and viral protein expression and to suppress host immune functions. To better define how this multifunctional protein can facilitate distinct functions, we characterize SARS-CoV-2 Nsp1 by using a combination of biophysical techniques, including light scattering, circular dichroism, hydrogen/deuterium exchange mass spectrometry (HDX-MS), and temperature-dependent HDX-MS. Our results reveal that the SARS-CoV-2 Nsp1 N- and C-terminus are unstructured in solution, and in the absence of other proteins, the C-terminus has an increased propensity to adopt a helical conformation. In addition, our data indicate that a short helix exists near the C-terminus and adjoins the region that binds the ribosome. Together, these findings provide insights into the dynamic nature of Nsp1 that impacts its functions during infection. Furthermore, our results will inform efforts to understand SARS-CoV-2 infection and antiviral development.